Territorial Identity and Grassroots Economic Activism: The Politicization of Farmers’ Mobilizations in the French Basque Country - Itçaina, Xabier; Gomez, Armelle (PARTECIPAZIONE E CONFLITTO, 2015)
The French Basque Country (FBC) represents an emblematic case of the politicization of local development through grassroots economic activism. These mobilizations are particularly obvious in the agricultural sector. Based on a qualitative research on small farmers’ organizations and short food circuits, this article shows that Basque farmers’ mobilizations constitute a case of a dual politicization of small-scale farming and territorial identity. This process has gone through two phases: the first period (1970-2000) was characterized by the politicization of local productive systems. Throughout the decade 2000-2010, a new mode of grassroots economic activism emerged, signalled by new alliances between producers and consumers, and by an increasing ideological pluralism. Two case studies illustrate these developments. The first relates to a case of explicit politicization with the controversy around the foundation in 2005 of an alternative Basque Chamber of Agriculture. The second case study is devoted to the development of short food circuits in the FBC, considered here as a case of implicit politicization of the encounter between productive and consumption circuits. Both cases illustrate the politicization of new economic social movements, and the constant overlapping of sectoral and territorial claims in the Basque territory.